BROOD REARING HABITAT USE BY WILD TURKEY HENS IN SOUTHCENTRAL SOUTH DAKOTA - Kevin F. McCabe; Lester D. Flake (Wildlife Society Bulletin)
Abstract: Brood rearing habitat use by wild turkey (Meleagris gallopavo merriami and M. g. intermedia) hens with broods and those without in Gregory County, South Dakota, was determined in order to formulate management suggestions for a grassland/riparian woodland habitat. Two hens with broods and 12 hens without broods were studied through telemetry and direct observations from 5 July through 17 August 1982 and 1983. Hens with broods grouped as <4 weeks of age selected for the grass/forb‐dominated understory and 52% average open canopy of south‐facing woodlands. In the 4‐6 week age group, hens with broods selected for the shrubby understory and 7% average open canopy of north‐facing bur oak forest. Hens with broods did not appear to use cultivated fields, farmsteads, or bottomlands, and grasslands were avoided or used in proportion to availability. Hens without broods used cultivated fields, farmsteads, and bottomlands in proportion to availability, generally avoided grasslands, and selected woodlands.